The Effect of Giving Tens and Tendon Glidess Exercise on Increasing Hand Functional Ability in Carpal Tunnel Syndrome Sufferers at RSU Nurussyifa Kudus - Lisnawati, Lisnawati; Fransisca Xaveria Hargiani; Rachma Putri Kasimbara; Nurul Halimah (Sean Institute, 2023)
Carpal tunnel syndrome is a wrist disorder caused by compression of the median nerve in the carpal tunnel. This disorder is characterized by hand pain at night, paralysis of the fingers, and weakness and atrophy of the thenar muscles innervated by the middle nerve. The physiotherapy measures given for CTS problems in this study were TENS and tendon glides exercise. This action aims to restore functional activity of the hand, reduce edema, and reduce pain. This type of research is a one group pre-test and post-test design consisting of 30 respondents with a purposive sampling method. The first observation was a special examination of CTS sufferers using wrist and hand disability index data forms. Second, provide a treatment program using the TENS (transcutaneous electrical nerves stimulation) method and tendon glides exercise. The sample for this research consisted of 30 respondents. From the results of the hypothesis test, it was obtained that 0.000<0.05. So the results of this therapy show a significant increase in hand functional ability between before and after therapy. Based on these results, the intervention given was TENS and tendon glides exercise to improve the functional ability of the sufferer's hands.